Burrata cheese: Trends over the last decade and future research - SOARES, Wisla Kívia de Araújo; CAVALCANTI, Mônica Tejo; ALVES, Rerisson do Nascimento; PEREIRA, Emmanuel Moreira; RIBEIRO, Neila Lidiany; GONÇALVES, Mônica Correia (Food Science and Technology, 2024)
Burrata is a delicate pasta filada cheese with a creamy filling. A bibliometric review of the last 10 years in Web of Science revealed a constant increase in articles on the production of this cheese, with Italy leading in the number of publications. The Journal of Dairy Science was the lead journal. The keywords that stood out the most were “Milk,” “Proteolysis,” and “Pasta filata cheese.” Italian universities have developed studies on microbiological and technological aspects to improve the quality and shelf life of Burrata. However, this bibliometric analysis identified future trends and collaborations in Burrata cheese research.